Cameroonian nursing students' attitudes towards older adults. (2020) - Wanko Keutchafo, Esther Lydie; Kerr, Jane
Abstract: Background: Studies have examined nurses' attitudes towards older people (ATOP), yet only a few were conducted in African countries. Objectives: To examine the nursing students' ATOP in Cameroon. Methods: A cross-sectional descriptive study was conducted. The sample consisted of 316 nursing students registered in two nursing schools. Data were collected between March and April 2018 using both English and French versions of Kogan's attitudes towards old people scale. Results: The results showed a slightly positive ATOP. The average positive attitude score was 60.41 (±8.69), the negative attitude score was 53.23 (±8.78), and the total score was 113.65 (±10.63). Cronbach's coefficient was 0.66 for the English scale and 0.62 for the French version. Some sociodemographic characteristics were statistically associated with students' ATOP. Conclusion: The results indicate that nursing students have a slightly positive ATOP. Geriatric courses should be included in nursing curricula to create a more positive ATOP among nursing students. The psychometric properties of the French version of the Kogan's scale should be sought.